(untitled) (Journal of Current and Advance Medical Research, 2025)
Laparoscopic inguinal hernia repair using the Totally Extraperitoneal (TEP) method represents a significant advancement in minimally invasive surgery. In the context of Bangladesh, where open hernia repair remains prevalent due to limited resources and training, the adoption of TEP offers a promising shift toward enhanced patient outcomes. This technique minimizes postoperative pain, reduces infection risks, and shortens recovery time, making it especially beneficial in high-volume surgical centers. Despite challenges such as cost and the need for specialized training, early experiences from select Bangladeshi institutions suggest that with appropriate investment in infrastructure and education, TEP can become a standard of care. Journal of Current and Advance Medical Research, January 2024;11(1):56-59